Windows 8 XAML primer - Liberty, Jesse (Expert's voice in XAML., 2012)
Windows 8 XAML Primer is a fast-paced introduction to XAML for Windows 8 developers who are already proficient C♯ coders. It introduces you specifically to the world of XAML development for Windows 8 apps in a practical, hands-on way - so you'll be building apps from the very first pages. Building on your existing C♯ knowledge, you're introduced to XAML from the ground up - what it is, what it does, and why it's important in Windows 8 development. You'll quickly learn how to use XAML efficiently within Visual Studio. You'll find practical coding quickstarts to get your XAML hands-on knowledge up to speed, so you'll be ready to progress to your more advanced Windows 8 programming projects with ease. If you're confident in your .NET coding abilities but the jump to XAML and C♯ in Windows 8 is giving you pause, then Windows 8 XAML Primer will have you coding Windows 8 projects in its first pages, and you'll be ready to start your own apps by the time you're finished.